2004
DOI: 10.1007/s00430-004-0229-y
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 is required for the progression of cutaneous lesions and neutrophil attraction in Leishmania major infection

Abstract: To elucidate the role of complement-mediated uptake in Leishmania major infection in vivo, transgenic BALB/c mice that express the cobra venom factor (CVF) under control of the alpha1-antitrypsin promoter were infected. CVF expression in these mice leads to a continuous activation and subsequent consumption of complement C3 in the serum. In contrast to susceptible non-transgenic BALB/c mice, CVF-transgenic mice are highly resistant to L. major infection and show a significantly reduced parasite dissemination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Although neutrophils are among the first cells recruited to L. major lesions and neutrophils have been shown to play some role in inducing protection (33, 34), several reports previously demonstrated that persistent inflammation characterized by increased neutrophil infiltration promoted disease susceptibility in BALB/c mice (16, 17, 35). Increased numbers of neutrophils were identified in established lesions in susceptible mice as compared to those of genetically resistant animals (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Although neutrophils are among the first cells recruited to L. major lesions and neutrophils have been shown to play some role in inducing protection (33, 34), several reports previously demonstrated that persistent inflammation characterized by increased neutrophil infiltration promoted disease susceptibility in BALB/c mice (16, 17, 35). Increased numbers of neutrophils were identified in established lesions in susceptible mice as compared to those of genetically resistant animals (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…PTX3 binding of C1q results in activation of the classical complement pathway. The formation of the C1 complex and of antigen-immune complexes entails increased phagocytic activity of monocytes and macrophages, secretion of immunoglobulins by B lymphocytes, stimulation of oxidative metabolism in neutrophils, adhesion of immune complexes to endothelial cells, and increased clearance of apoptotic cells [25]. Like histones, pentraxin co-localized to NETs seems to be a central molecule in promoting local antimicrobial immune responses [8].…”
Section: The Physiological Role Of Neutrophils and Nets In Innate Immmentioning
confidence: 99%
“…Upon infection, these mice did not develop any inflammatory lesions and had lower neutrophil infiltration at the site of infection [34]. It remains difficult to assess if such decreased neutrophil recruitment is the cause or the result of the observed inhibition of lesion development.…”
Section: Neutrophils As Orchestrators Of the Immune Responsementioning
confidence: 99%